Development of landmark based routing system for in-car GPS navigation - Zeeb, Benjamin; Kong, Qingling; Xia, Jianhong (Cecilia); Chang, Elizabeth (IEEE Inc., 2013)
Research has shown that where possible humans will incorporate landmarks as part of a cognitive map for the purposes of navigation. This paper discusses an extension of existing GPS navigation device design to include landmark-based instructions. This is achieved through the use a landmark weighting system to influence routes chosen by a traditional GPS navigation system, namely, shortest distance routing algorithm. This system applies the landmark weights to nodes of a network graph in addition to replacing distance-to-turn type directions where appropriate. The proposed landmark-based routing system is flexible for a wide range of situations as users can customize the landmark selection and routing parameters to fit specific needs.